34 Culprit coronary arteries in stable angina and unstable coronary artery disease have more vulnerable features when compared to non-culprit coronary arteries. (24th April 2016) - Koganti, S; Karanasos, A; Kotecha, T; Patel, N; Loder, CD; Lockie, T; Regar, E; Rakhit, RD
Abstract : Aims: To compare optical coherence tomography (OCT)-derived plaque characteristics of the culprit and non-culprit coronary arteries in patients with Non ST elevation myocardial infarction (NSTEMI) and stable angina pectoris (SA). Methods: Assessment of clinical data, angiographic, and OCT imaging including the analysis of plaques was performed. Plaque composition, thickness, arc, length, volume and relative volume were recorded. The presence of thrombus, microvessels, macrophages, cholesterol crystals and calcific nodules were recorded (in percentage of frames) as well. Results: To date, 12 patients (8 NSTEMI and 4 SA) were included and analysed. Mean age of this predominantly male group was 55.36 ± 7.9 years. In total OCT was performed in 31 coronary arteries (12 culprit and 19 non culprit) - corresponding to a total of 1992 frames were analysed. Artery level analysis revealed a higher lipid content in culprit arteries as documented by a wider maximum lipid arc (221.91 ± 87.5 vs. 139.2 ± 42.0; p = 0.009) and higher relative lipid volume index (6.35 ± 4.8 vs. 3.3 ± 2.8; p = 0.08). Furthermore, in culprit arteries average cap thickness was smaller (340μ±41μ vs. 400μ±81μ; p = 0.03), and the incidence of macrophages was higher (% of frames 7.8 ± 6.2 vs. 3.2 ± 4.6; p = 0.02). Conclusions: In this three-vessel OCT study culprit arteries in both NSTEMI and SA were noted to have more vulnerable features than non-culprit arteries however, larger studies are required to establish this finding.